Systematic review of the association between talc and female reproductive tract cancers - Lynch, Heather N.; Lauer, Daniel J.; Leleck, Olivia Messina; Freid, Rachel D.; Collins, Justin; Chen, Kathleen; Thompson, William J.; Ierardi, A. Michael; Urban, Ania; Boffetta, Paolo; Mundt, Kenneth A. (Frontiers in Toxicology, 2023)
Talc is a hydrous magnesium sheet silicate used in cosmetic powders, ceramics, paints, rubber, and many other products. We conducted a systematic review of the potential carcinogenicity of genitally applied talc in humans. Our systematic review methods adhere to PRIMSA guidelines and incorporated aspects from the US Institute of Medicine (IOM, now the National Academy of Medicine) and several US EPA frameworks for systematic reviews, evaluating and integrating the epidemiological, animal, and mechanistic literature on talc and cancer. We conducted a comprehensive literature search. Detailed data abstraction and study quality evaluation, adapting the Toxic Substances Control Act (TSCA) framework, were central to our analysis. The literature search and selection process identified 40 primary studies that assessed exposure to talc and female reproductive cancer risks in humans (n = 36) and animals (n = 4). The results of our evaluation emphasize the importance of considering biological plausibility and study quality in systematic review. Integrating all streams of evidence according to the IOM framework yielded classifications of suggestive evidence of no association between perineal application of talcum powders and risk of ovarian cancer at human relevant exposure levels. We also concluded that there is suggestive evidence of no association between genital talc application and endometrial cancer, and insufficient evidence to determine whether a causal association exists between genital talc application and cervical cancer based on a smaller but largely null body of literature.